Sept défis stratégiques pour le secteur des services financiers au Québec - Ménard, L. Jacques (Assurances, 1995)
Over the past 15 years, financial services have perhaps experienced the most sweeping changes of all economic sectors in Canada. The author, Mr. L. Jacques Ménard, Vice Chairmain of Nesbitt Burns, begins by tracing the first key events in the late 1960s that have led to the crumbling of barriers between the four pillars in Canada. He then describes the major trends prevailing in Québec's financial services sector and looks at the risks which threaten to reshape the market. He concludes with the major strategic challenges faced by financial institutions in a fiercely competitive environment.